ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-V/2007 TENTANG MEKANISME PEMBENTUKAN PENGADILAN AD HOC DALAM PELANGGARAN HAM DI INDONESIA - Muhammad Roziki (Dinamika, 2020)
ABSTRACTLaw Number 26 of 2000 concerning Human Rights Courts. This regulation is responsive, considering that there have been many past gross human rights violations involving state institutions. However, there are legal problems when in Article 43 Paragraph (2) of the Human Rights Court Law which explains that a Human Rights Court is formed on the basis of "allegations" by the Parliament and is determined by the Presidential Decree. Erico Guterres thought that such a matter was too political in nature, therefore this regulation was submitted for judicial review to the Constitutional Court. This research is a normative legal research, which is carried out by examining library materials, which are secondary data and legislation as primary legal materials. This research is a statutory approach, a legal case approach, a conceptual approach. Based on this research, several problems were found, namely, why was Law Number 26 of 2000 concerning the Human Rights Court filed for judicial review to the Constitutional Court? What is the ratio of the Constitutional Court to the decision in Decision Number 18 / PUU-V / 2007 regarding the mechanism of establishing an ad hoc court in human rights cases in Indonesia?Keywords : Human rights court, Judicial review, Constitutional court.ABSTRAKUndang-undang Nomor 26 tahun 2000 tentang Pengadilan Hak Asasi Manusia. Regulasi ini merupakan suatu hal yang responsif, mengingat banyak kejadian pelanggaran HAM berat di masa lalu yang melibatkan institusi negara. Namun terdapat problematika hukum ketika dalam Pasal 43 ayat (2) UU Pengadilan HAM yang menjelaskan bahwa pengadilan HAM dibentuk atas dasar “dugaan” oleh DPR dan ditetapkan oleh Keppres. Hal yang demikian dianggap terlalu bernuansa politik oleh Erico Guterres, maka oleh sebab itu regulasi ini diajukan uji materil ke Mahkamah Konstitusi. Penelitian ini adalah penelitian hukum normatif, yang dilakukan dengan cara meneliti bahan pustaka, yang merupakan data sekunder dan aturan perundang-undangan sebagai bahan hukum primer. Penelitian ini Pendekatan Perundang-perundangan, Pendekatan Kasus Hukum, Pendekatan Konseptual. Berdasarkan penelitian tersebut ditemukan beberapa masalah yakni, Mengapa Undang-undang Nomor 26 tahun 2000 tentang Pengadilan Hak Asasi Manusia diajukan Uji materil ke Mahkamah Konstitusi? Apa ratio decidendi Mahkamah Konstitusi dalam putusan Nomor 18/PUU-V/2007 tentang mekanisme pembentukan pengadilan ad hoc dalam perkara HAM di Indonesia?Kata Kunci : Pengadilan HAM, judicial review, Mahkamah Konstitusi.